Shear stress studies of plasma-sprayed teeth derived hydroxyapatite on titanium - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
The purpose of this study was to develop a biologically derived fluor rich hydroxyapatite (HA) for plasma spraying purposes by a simple way. HA was derived from human teeth and processed in laboratory conditions as plasma coating material. For manufacturing data HALL flowability, shear stress, SEM, metallography, X-ray diffraction and ion analyzing tests were performed. Implant prototypes were prepared from titanium rods, which were coated with HA powder with a plasma coating unit. Statistical studies were also done to test the performance for plasma coatings. All results showed that this production method enables the manufacturing of HA powders with biological origin for plasma spraying purposes compared with other time consuming and delicate methods. Powder morphology developed by selective grinding process was a key parameter to start such a production line in industry.
Keywords: Hydroxyapatite; Plasma Spray; Shear Stress; Teeth-Derived Hydroxyapatite